1999
DOI: 10.1046/j.1365-2249.1999.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by vitamin B12: augmentation of CD8+ T lymphocytes and natural killer (NK) cell activity in vitamin B12-deficient patients by methyl-B12 treatment

Abstract: SUMMARYIt has been suggested that vitamin B12 (vit.B12) plays an important role in immune system regulation, but the details are still obscure. In order to examine the action of vit.B12 on cells of the human immune system, lymphocyte subpopulations and NK cell activity were evaluated in 11 patients with vit.B12 deficiency anaemia and in 13 control subjects. Decreases in the number of lymphocytes and CD8 þ cells and in the proportion of CD4 þ cells, an abnormally high CD4/CD8 ratio, and suppressed NK cell activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
162
1
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(174 citation statements)
references
References 18 publications
5
162
1
6
Order By: Relevance
“…Vitamin A deficiency has also been shown to reduce the CD4 ϩ cell proportion in humans (39). A few in vivo studies showed a decrease in CD8 ϩ cell population with deficiencies in vitamin D (40), vitamin E (41), and vitamin B12 (42)(43)(44). Interestingly, vitamin B12 plays an important role in DNA metabolism and B12 deficiency can cause uracil misincorporation into DNA by the same mechanism as folate deficiency…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A deficiency has also been shown to reduce the CD4 ϩ cell proportion in humans (39). A few in vivo studies showed a decrease in CD8 ϩ cell population with deficiencies in vitamin D (40), vitamin E (41), and vitamin B12 (42)(43)(44). Interestingly, vitamin B12 plays an important role in DNA metabolism and B12 deficiency can cause uracil misincorporation into DNA by the same mechanism as folate deficiency…”
Section: Discussionmentioning
confidence: 99%
“…A considerably suppressed NK cell activity was also noted in humans with B12 deiciency [35], as well as a decrease in the spleen NK activity was observed in rats on B12-deicient diet, although this efect was not statistically signiicant in the thymus or axillary nodes [36].…”
Section: Speciic Role Of Vitamin B12 In Immune System Functioningmentioning
confidence: 82%
“…In contrast, serum levels of immunoglobulins are not afected by vitamin B12 deiciency or supplementation [35].…”
Section: Speciic Role Of Vitamin B12 In Immune System Functioningmentioning
confidence: 98%
See 2 more Smart Citations